THE NECESSITY OF IDIOMATIC EXPRESSIONS TO ENGLISH LANGUAGE LEARNERS - Abushaev Amir Kamilevich (Journal Park Publishing, 2023)
Non-native speakers of English are found in different parts of the world. The usage of Idiomatic expressions by those speakers are considered as an important issue and is regarded as an essential part of the English Language competence. It is a necessity that all speakers of the English Language become aware and proficient in using English idiomatic expressions. It is essential and is considered a big part of English language proficiency to be able to use idiomatic expression when communicating in the English Language. However, many English learners, especially those of Arabic origin, lack the competence to use English idiomatic expressions adequately. This paper aims to discuss the importance of idiomatic expressions to English language learners. In this paper, personal suggestions have been reached for better idiomatic comprehension and acquisition. Contributions have been made by the author regarding the importance of understanding and how to better use idioms.
Keywords: Idiomatic expressions, native speakers, non-native speakers, linguistics.